The beginner's guide to opera stage management : gathering the tools you need to work in opera - Ranno, Danielle (New York, NY : Routledge, 2023)
"The Beginner's Guide to Opera Stage Management is the first book to cover theatrical stage management practices specifically for opera productions, providing an invaluable step-by-step guide. Beginning with a brief history of opera and detailing its difference from musical theatre, the book covers stage management best practices through prep, rehearsals, tech, performance, and wrap up. From the moment a manager accepts a contract, right through to archiving paperwork, this essential toolkit covers each step of a stage manager's journey. Working with a score, reading music, working with singers, conductors, and musicians, basic duties of a stage manager versus an assistant stage manager, and other tasks specific to opera are also included in this comprehensive guide. This book is full of tips and tricks, as well as the good, bad, and ugly stories from opera stage managers, sharing both their experiences and mistakes. This is the perfect how-to book for the professional or emerging stage manager looking to work in opera, or to expand their existing stage management skillset"--
Opera Background -- Document Design -- Prep Week -- Rehearsal -- Rehearsal Paperwork -- Tech Week -- Performance -- Archive.
Includes index.
"A Focal Press book" -- cover.
Keywords: Opera -- Production and direction; Stage management; PERFORMING ARTS / Theater / Direction & Production; MUSIC / Genres & Styles / Opera; PERFORMING ARTS / General